Pomorski putnički prijevoz na Jadranu u funkciji razvoja turizma - DELIBAŠIĆ, Tatjana (Promet - Traffic&Transportation, 2026)
PASSENGER SERVICES ON THE ADRIATIC IN THE SERVICE OF TOURIST TRADE DEVELOPMENT This paper deals with the meaning and current status of traffic links between the coastal area and the islands from the aspect of economic, tourist and demographic development of the islands, serving the author to expose subsequently the fact that the combined transport on the mainland–islands route has been assigned inadequate attention while the positive examples of some other countries have not been followed as fully as required. The author sees our chance in the development of nautical tourism in the light of world-wide tendencies and attractiveness of our coast and advocates the advancement of this industry.